2012
DOI: 10.3390/ijms131114707
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Toninia candida and Usnea barbata Together with Their Norstictic Acid and Usnic Acid Constituents

Abstract: The aim of this study was to investigate the chemical composition of acetone extracts of the lichens Toninia candida and Usnea barbata and in vitro antioxidant, antimicrobial, and anticancer activities of these extracts together with some of their major metabolites. The chemical composition of T. candida and U. barbata extracts was determined using HPLC-UV analysis. The major phenolic compounds in these extracts were norstictic acid (T. candida) and usnic acid (U. barbata). Antioxidant activity was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 27 publications
10
77
3
Order By: Relevance
“…The strong antimicrobial activities of evernic and norstictic acids have previously been reported [4,17]. They observed that they both exerted antibacterial activity against Gram-positive and Gram-negative bacteria, but Gram-negative bacteria were more resilient.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The strong antimicrobial activities of evernic and norstictic acids have previously been reported [4,17]. They observed that they both exerted antibacterial activity against Gram-positive and Gram-negative bacteria, but Gram-negative bacteria were more resilient.…”
Section: Discussionmentioning
confidence: 96%
“…Also, total reactive antioxidant potential and total antioxidant reactivity analysis indicate that atranorin acts as a general antioxidant, although it appeared to enhance peroxyl radical-induced lipoperoxidation in vitro [16]. Similarly, strong antioxidant activities were found for salazinic, protocetraric, evernic and norstictic acids [4,5,17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In most lichens, phenols are important antioxidants because of their ability to scavenge free radicals such as singlet oxygen, superoxide and hydroxyl radicals (Shanab et al 2011). Numerous researches reported a significant correlation between antioxidative activities of lichens and phenolic content (Behera et al 2009;Ranković et al 2012). However, some authors believe that the antioxidant activity of extracts may not necessarily correlate with the content of polyphenolics (Odabasoglu et al 2004), suggesting that the antioxidant activity of different lichens may also depend on other, non-phenol components.…”
Section: Resultsmentioning
confidence: 99%
“…This may be primarily responsible for the antimicrobial activity demonstrated in this study and others (Burkholder et al 1944, Carrazzoni 1975, Huovinen & Ahti 1986, Ahti et al 1993, Lauterwein et al 1995, Pereira et al 1997, Honda & Vilegas 1998, Yano-Melo et al 1999, Donlan 2001, Falcão et al 2004, Ribeiro et al 2006, Moura et al 2008. Ranković et al (2012) tested the antibacterial activity of usnic acid compared to streptomycin for Bacillus mycoides (ATCC 6462), B. subtilis (ATCC 6633), S. aureus (ATCC 25923), Escherichia coli (ATCC 25922), and Klebsiella pneumoniae (ATCC 13883). They observed that usnic acid obtained similar or stronger activity than the isolates tested with streptomycin.…”
Section: Determination Of Antibacterial Activity Of Organic Extract Omentioning
confidence: 99%